Funding criteria and project performance of the food security projects in the Sedibeng District Municipality - Mantena, Z. I.; Mofokeng, W. N.; Mzini, L. B. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
This paper assesses the criteria for funding food security projects and the performance of the respective projects in the Gauteng Province with reference to the Sedibeng District Municipality. Food security is often described as one of the fastest growing social movements. This study seeks to understand the criteria applied to fund the projects. Furthermore, the study assesses the project performance which is a requirement for outcome measurement frameworks. A qualitative research is applied to comprehend the context of pro-poor funding and project performance. Semi-structured interviews were conducted in the Gauteng Department of Agriculture and Rural Development and the Sedibeng District Municipality. The paper concludes with a set of recommendations to enhance food security initiatives. Conducting successful funding on projects, consistently and repeatedly, is still a challenge for many organisations. The paper concludes that structured financing on food security projects leads to a proportionally higher investment in poverty alleviation. The study suggests that it is necessary to increase funding on investment for sustainable food security projects.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Food security; Food security programme; Funding criteria; Project performance; Food security -- South Africa; Finance, Public -- South Africa; Local government -- South Africa